2007
DOI: 10.1016/j.addbeh.2006.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of substance use and subsequent risk factors related to suicide among urban high school students

Abstract: Objective-To examine the association between onset of substance use and risk factors related to suicide.Method-1,252 adolescents in two urban school districts completed surveys as part of a large, randomized controlled prevention effectiveness trial. Risk factors measured included depressive symptoms, suicide ideation, suicide ideation specifically with alcohol and/or drug use, endorsement of suicide as a personal option, and suicide attempt.Results-In our final multivariate models that controlled for current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 36 publications
7
74
3
1
Order By: Relevance
“…27,28,30 It is a robust finding that debut age of drug use predicts later substance abuse and future engagement in additional health risk behaviors. 31,32 Additional consequences of early substance use may be reflected in increased suicide risk, 33 which itself represents a significant proportion of young adult and adolescent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…27,28,30 It is a robust finding that debut age of drug use predicts later substance abuse and future engagement in additional health risk behaviors. 31,32 Additional consequences of early substance use may be reflected in increased suicide risk, 33 which itself represents a significant proportion of young adult and adolescent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…One of a few studies to examine the effects of adolescent PDM on adult outcomes found that early adolescent PDM was a signifi cant predictor of PDM and abuse/dependence on prescription drugs in adulthood (McCabe et al, 2007b). Although there is limited research on the long-term consequences of adolescent PDM, adolescent substance use, in general, is associated with adverse outcomes, including lower academic achievement (Ellickson et al, 2004), delinquency (D'Amico et al, 2008), unprotected sexual inter-course and unplanned pregnancy (Stueve and O'Donnell, 2005), and suicide risk (Cho et al, 2007). Longitudinal research suggests that adolescent substance use also increases risk for criminality (Stenbacka and Stattin, 2007), unemployment (Rohde et al, 2007), and substance-use disorders and psychiatric dysfunction (Brook et al, 2002) in adulthood.…”
mentioning
confidence: 99%
“…The relationships between suicidal behaviour and early tobacco use, 4,7,8,40 alcohol consumption and cannabis use 3-10 have long been known. Here however, after adjustment, the association decreased slightly or was no longer significant after adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…2 Tobacco, alcohol, and cannabis use have been shown to be associated with suicidal behaviour in adolescents. [3][4][5][6][7][8][9][10] Until now, the association between suicidal behaviour and kava has not been examined. Kava, a psychoactive substance commonly used by youth in New Caledonia is also drunk elsewhere in the region including Australia and New Zealand, where its use has been documented in Aboriginal and Pacific Island communities.…”
mentioning
confidence: 99%